The Influence of The Interest Rate (BI Rate) and Non Performing Loan (NPL) To The Distribution of Banking Credit in Bengkulu Province in The Years 2013-2015 - Damarsiwi, Eska Prima Monique (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
Banks collect funds from the public in the form of deposits and are distributed back in the form of credit to companies and individuals. This study is aimed to determine the effect of the BI Rate and Non-Performing Loans (NPL) to the capital loan in Bengkulu province in the years 2013-2015. Before doing the multiple regression analysis, the data should be free from the classical assumption.The empiricalresults of this partial analysis show that the variable BI Rate istcount(2.402) >ttable (2,228),this meansthat the BI Rate has a positive effect on bank lending in the province of Bengkulu. Variable Non perfoming loans (NPL) aretcount (2.531)>ttable (2,228) and sig. (0,037) < alpha (0.05), the variable Non-Performing Loan (NPL) revealed a positive and significant effect on bank lending in the province of Bengkulu. Simultaneously the variable BI Rate and Non-Performing Loans (NPL) have the values of F (11.336)> F table (4.96) with sig (0.003) <α (0.05), it means that the variable BI Rate and Non-Performing Loan (NPL) simultaneously / concurrently affect the dependent variable. The result also shows the ability of a model prediction of65.3% while the remaining34.7% are influenced by other factors outside the model that has not been incluioded in the study. Meanwhile the most dominant variable in the study is the variable BI Rate which has a value of the partial coefficient of 62.5%. JEL Classification: E43, E52, E58Keywords: BI Rate, Capital Loan, Non-Performing Loans